(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
With the growing housing crisis and the exclusion of marginalized segments of society, and the disparity of social housing from one country to another in terms of types, models, providers, and the targeted categories it serves, and with the emergence of local legislation to include it in the housing projects of the new cities planned to be established in Iraq, and with the newness of the country’s with it and the absence of a specific conceptual basis for local social housing, it was deemed necessary to develop a conceptual framework closer to a local profile for social housing, to define its criteria and make it possible to distinguish it from other housing categories, and to understand its roots and stages of development, from following the modern approach to designing cities that support mixed use and density without overcrowding, based on the principle of design for everyone.The research methodology relied on data collection, inventory, and analysis for comparison, addressing the most significant problems faced by social housing and proposing solutions through calls for renewal and adaptive use of social housing in a contemporary style.Th research concluded with a specific knowledge framework, formulating a clear and integrated definition of local comprehensive social housing and identifying its main types and the most important targeted categories served by the general targeting approach.